Rancangan Pengembangan Modul Penggajian pada Sistem Informasi Akuntansi Terintegrasi dengan Kerangka Kerja COSO - Sriyanti Sriyanti (Syntax Idea)
PT XYZ is a food and beverage trading company, in its business process it has implemented SIA for purchasing, sales, accounts payable, accounts receivable, bank cash, inventory and general ledger modules. The company has 200 employees, while the payroll system is still done manually, which can increase the risk of errors and fraud. The accounting cycle related to payroll is the HR/Payroll cycle. This study aims to determine the extent to which the current payroll system procedures are effective in terms of internal controls, identify weaknesses in internal control of payroll procedures and provide alternative solutions to correct existing weaknesses. The data analysis technique uses interactive analysis as standard for the Committee of Sponsoring Organizations (COSO) framework, then creates a new development plan for the payroll module in an integrated SIA based on COSO standards. This research uses an experimental method, its development uses the Object Oriented Analysis Design (OOAD) method, which is oriented towards model development using the Unified Model Language (UML) facility. The results of the study indicate that there are weaknesses in the form of errors in reporting, reporting takes a long time and payroll controls are still weak. Solving the problem to overcome these weaknesses requires improving the payroll system and developing a new computer-based payroll system that is integrated with the existing SIA, so that the developed system can be used efficiently and effectively.